GIANT PITUITARY ADENOMA WITH NORMAL VISION AND MISLEADING RADIOLOGICAL FINDINGS - muhammad, khalid; Raina, Umer Farooq; Zaman, Khaleeq uz; Tahir, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Giant pituitary adenomas are rare and present with visual loss.Giant pituitary adenoma has rarely been reported presenting with normal vision.We report Giant pituitary adenoma with Normal vision in a 35 years old patient presenting with adult onset epilepsy and headache.